MODEL PELAYANAN PUSKESMAS (PUSAT KESEHATAN MASYARAKAT) DI KOTA SEMARANG - Imam Gozali (MEDIA, 2012)
The purpose of this research is making a model of health center services (Community Health Center) in Semarang. The variables that be used are perception, image, service quality, customer satisfaction and customer loyalty. The population in this study are people in Semarang who ever went to the health center. Samples were taken 8 (eight) health centers in Semarang that have services and excellent programs with purposive informant. The results are first, the performance of health centers is still weak, because there are many people who come to the hospital for treatment. Second, service is slow, so it becomes the main target ofÂ health department in terms of administrative proceedings and services to patients quickly, it did not take long, though it is still difficult to realize. Third, in public opinion, the image ofÂ health centers are still not good enough,